Application of Leadership Style to the Management of PT Trias Sentosa - Yoga Dian Pratama (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The purpose of this study was to determine the application of leadership style at PT Trias Sentosa to the company's management. Every company certainly has a leader, where his leadership will affect employee performance. Based on leadership theory, that a leader has a big influence on the good and bad development of a company. The method in this research uses descriptive qualitative research. The results of the research on the application of leadership to the management function at PT. Trias Sentosa, Tbk, namely: 1) setting the direction of business goals and targets, 2) developing strategies in achieving these goals and targets, 3) determining the required resources, 4) setting standards of success in achieving business goals and targets.